Diffuse Recurrence of Hepatocellular Carcinoma After Liver Resection: Transarterial Chemoembolization (TACE) Combined With Sorafenib Versus TACE Monotherapy - Yao, Wang; Xue, Miao; Lu, Mingjian; Wang, Yu; Zhao, Yue; Wu, Yanqin; Fan, Wenzhe; Li, Jiaping (Frontiers in Oncology, 2020)
This study aims to compare the effectiveness and complications of transarterial chemoembolization (TACE) combined with sorafenib (S-TACE) and TACE monotherapy in HCC patients with diffuse recurrence (DR). This retrospective study was approved by our hospital ethics committee, and all patients provided informed consent. We retrospectively enrolled 356 DR patients from January 2005 to December 2014, who underwent either S-TACE or TACE monotherapy. Treatment complications, overall survival (OS) and progression-free survival (PFS) were evaluated. Survival curves were constructed using the Kaplan-Meier method and compared using a log-rank test. Our results found a significant difference between S-TACE and TACE monotherapy in the PFS and OS of HCC patients with early diffuse recurrence (EDR) (p=0.011 and 0.049, respectively). Patients with late diffuse recurrence (LDR) who underwent S-TACE had longer OS (median 24.0 vs. 16.0 months; p=0.044) compared with those in the TACE monotherapy group. Subgroup analysis revealed that S-TACE therapy resulted in higher OS of EDR patients with tumors > 5 cm and HBV-DNA >100 (p=0.036 and 0.035, respectively), compared with patients given TACE monotherapy. S-TACE therapy also resulted in better OS in LDR patients with AFP≥400 ng/ml, AFP<400 ng/mL, TB<28 g/L, TB>28 g/L, and a maximum tumor diameter < 5 cm (p=<0.001, 0.042, <0.001, <0.001, and <0.001, respectively). The rate of major complications in patients who underwent S-TACE was not significantly different to those who underwent TACE monotherapy (33.5% vs. 28.2%, p= 0.69). Overall, patients given S-TACE had better OS in both EDR and LDR patients, but only EDR patients had better PFS.